HUSBAND SUPPORT AND HEALTH WORKERS SUPPORT ON IVA EXAMINATION PRACTICES IN FERTILE AGE WOMEN - Kurniati, Paskalia Tri (Krafon Publishing, 2019)
Early detection of cervical cancer is an innovative breakthrough in health development to reduce mortality and morbidity due to cervical cancer. Until 2016 there was a decline in visits of fertile age women to conduct IVA screening to Tanjung Puri Health Center, but in 2017 there were 2 people with positive IVA. This study aims to determine the relationship of husband's support and support of health workers with the practice of IVA examination at fertile age women. This research method is a type of non-quantitative quantitative research using a correlation study approach (cross sectional). The sample in this study was taken by accidental sampling in the first week of December, amounting to 57 fertile age women. The results showed that 9.6% of fertile age women had never done IVA examinations, 50.9% of fertile age women did not receive husband support and 54.4% of fertile age women received support from health workers. The conclusion is that there is a relationship between husband's support and the practice of IVA examination to conduct IVA examination. The results of statistical tests show that there is a relationship between husband support (p=0.016) and health care support (p=0.032) with the practice of IVA examination. Efforts are needed to improve the dissemination and effective and continuous way of delivering information by health workers to fertile age women and involve fertile age women couples to fully support the IVA examination.